The Journal of Engineering, Science and Technology (JESTEC): A Bibliometric Insight into Materials Research Trends and Innovation to Support Sustainable Development Goals (SDGs) - Abdulkareem Sh. Mahdi Al-Obaidi (Bumi Publikasi Nusantara, 2026)
This study presents a bibliometric analysis of materials-related research published in the Journal of Engineering Science and Technology (JESTEC) from its inception until 2025. The analysis covers publications indexed in Scopus from 2009 to July 2025, totaling 3,825 documents, of which a substantial subset is dedicated to materials science and engineering. Data were retrieved using JESTEC ISSN in the Scopus database and filtered using keywords such as “material”, in which this is appropriate to include term of materials engineering, composite, and nanomaterial. Findings reveal that materials science has become a significant research domain in JESTEC, with topics ranging from adsorption and composite fabrication to renewable materials and nanotechnology applications. The analysis also shows a growing alignment of research with the Sustainable Development Goals (SDGs), particularly in sustainable production, environmental protection, and energy efficiency. These results highlight JESTEC’s role as a platform for advancing interdisciplinary materials research and its contributions toward global sustainability targets.